Microheterogeneity of therapeutic monoclonal antibodies is governed by changes in the surface charge of the protein. Issue 12 (22nd November 2016) - Hintersteiner, Beate; Lingg, Nico; Janzek, Evelyne; Mutschlechner, Oliver; Loibner, Hans; Jungbauer, Alois
Abstract: It has previously been shown for individual antibodies, that the microheterogenity pattern can have a significant impact on various key characteristics of the product. The aim of this study to get a more generalized understanding of the importance of microheterogeneity. For that purpose, the charge variant pattern of various different commercially available therapeutic mAb products was compared using Cation‐Exchange Chromatography with linear pH gradient antigen affinity, Fc‐receptor affinity, antibody dependent cellular cytotoxicity (ADCC) and conformational stability. For three of the investigated antibodies, the basic charge variants showed a stronger binding affinity towards FcγRIIIa as well as an increased ADCC response. Differences in the conformational stability of antibody charge variants and the corresponding reference samples could not be detected by differential scanning calorimetry. The different biological properties of the mAb variants are therefore governed by changes in the surface charge of the protein and not by an altered structure. This can help to identify aspects of microheterogeneity that are critical for product quality and can lead to further improvements in the development and production of therapeutic antibody products. Abstract : Charge variants are an inherent characteristic of therapeutical mAb products. They can be separated at a preparative scale using cation exchange chromatography. In this study such chromatographically separated charge variant fractions were shown to exhibit varying antibody dependent cellular cytotoxicity (ADCC) activity but no differences were found with respect to conformational stability. It can therefore be concluded that the different biological properties of antibody charge variants are governed by changes in the surface charge of the protein and not by an altered structure.